Парижские тайны: роман :[перевод с французского Я. Лесюка и М. Трескунова] (Эжен Сю) - Сю Эжен (1993)
Экземпляры: Ф-24 (20210302) / Инвентарный номер: 96123 / Цена: / Сис.шифр: 84(4=471.1)-4 / Авт.знак: С 98 / ГРНТИ: 17.82.31 / ББК: 84(4=471.1)-4